Use Big Theory Clarifies Financial Performance: The Role of Internal Mechanisms Control - Magda Siahaan (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: This paper establishes the basic concepts, related work, and core propositions of implementing integrated Governance, Risk Management and Compliance (GRC), internal audit function, and financial performance through the perspective of the underlying grand theory. Method: This paper uses literature-based analysis. First, it builds a conceptual argument by looking for the big theory, which is the leading theory that serves as the foundation for explaining and analyzing important phenomena in a field of science, which can underlie the integration of GRC, internal audit, and financial performance. It concludes with the predicted relationships of the three that can be seen through their application. Big theory is the leading theory that serves as the foundation for explaining and analyzing important phenomena in a field of science. Findings: Based on underlying the big theory and the supporting concepts, it is proven that integrated GRC, internal audit, and financial performance are in one corridor of built relationships. Novelty/Value: Integration of GRC, internal audit, and financial performance in one agency theory-based framework presents integrated relationships and new hypotheses, different from previous studies that separate these variables.